Al3(Sc, Zr)-based precipitates in Al–Mg alloy: Effect of severe deformation. (1st February 2017) - Buranova, Yu.; Kulitskiy, V.; Peterlechner, M.; Mogucheva, A.; Kaibyshev, R.; Divinski, S.V.; Wilde, G.
Abstract: Precipitate evolution in an AA5024 Al-based alloy containing Sc and Zr is investigated in different states: as-cast, extruded and severely deformed. An overview of the microstructure is given and the evolution of particle size and morphology as a function of mechano-thermal processing is investigated, with an emphasis on the Al3 (Sc, Zr)-based precipitates. The precipitates are found to maintain their coherence with the matrix after the interaction with dislocations and low-angle grain boundaries as it is revealed by atomistic simulations and by the so-called Geometric Phase Analysis of the local strain fields. It is established that the precipitates can loose their coherency with the matrix during the severe plastic deformation, that decreases generally grain boundary pinning effect and promotes recrystallization. Graphical abstract: Image 1